2020
DOI: 10.1155/2020/6901678
|View full text |Cite
|
Sign up to set email alerts
|

Ifosfamide, Carboplatin, and Etoposide (ICE) in Combination with Regional Hyperthermia as Salvage Therapy in Patients with Locally Advanced Nonmetastatic and Metastatic Soft-Tissue Sarcoma

Abstract: Patients with localized relapse of soft-tissue sarcoma (STS) after anthracycline-based chemotherapy have a dismal prognosis, particularly when surgery is not possible. To facilitate resection and improve long-term tumor control, we applied an intensified perioperative treatment consisting of ICE (ifosfamide 6 g/m2, carboplatin 400 mg/m2, and etoposide 600 mg/m2) in combination with regional hyperthermia (RHT) to maximize local control. Here, we retrospectively evaluate the safety and efficacy of this strategy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The other study included 110 participants with locally advanced high-risk STS receiving combined chemotherapy and LRHT. 58 Disease control occurred in 59% of non-metastatic cases and 47% in those with metastases, with a median OS of 26 and 12 months, respectively.…”
Section: High-risk Soft-tissue Sarcoma (Sts)mentioning
confidence: 95%
See 1 more Smart Citation
“…The other study included 110 participants with locally advanced high-risk STS receiving combined chemotherapy and LRHT. 58 Disease control occurred in 59% of non-metastatic cases and 47% in those with metastases, with a median OS of 26 and 12 months, respectively.…”
Section: High-risk Soft-tissue Sarcoma (Sts)mentioning
confidence: 95%
“…One RCT (yielding three publications), [13][14][15] five observational studies [56][57][58][59][60] , and seven single-arm trials [61][62][63][64][65][66][67] were identified. Additionally, one single-arm trial 68 included deep seated sarcomas, and one observational study mixed soft tissue tumours.…”
Section: High-risk Soft-tissue Sarcoma (Sts)mentioning
confidence: 99%
“…However, in up to 50% of patients, distant metastases occur. In previous years, the median overall survival (OS) in the metastatic setting was reported to be 12 to 15 months [5,6]. More recently, median OS appears to have improved and ranged from 20 to 24 months in randomized trials [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regional heating of tissue can be induced with radiofrequency (RF) antennas that create a focus in the target area. This treatment modality has become part of clinical practice for the treatment of various cancer types, including the treatment of sarcoma patients and patients with cervical cancer 2‐4 . To prevent tissue damage by overheating, many procedures rely on temperature probes that are placed intraluminally or superficially onto the skin.…”
Section: Introductionmentioning
confidence: 99%